2018
DOI: 10.1210/jc.2017-02551
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of The American Joint Committee on Cancer 8th Edition T Staging System for Papillary Thyroid Carcinoma

Abstract: In our cohort, pT8 was inferior to pT7 in patients ≥55 years old without macroscopic ETE or distant metastases in whom T classification affects TNM stage. Microscopic ETE was strongly associated with other adverse prognostic factors and reduced DFS in this patient subgroup and may be an effective surrogate for disease biology in PTC, irrespective of whether it is an independent prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…Following the publishing of the 8th AJCC staging system, it also caused widespread controversy. Many researchers have presented different views against the new staging system, as they consider that mETE can increase the risk of thyroid carcinoma recurrence (45). In the 8th AJCC staging system, any lymph node involvement in either the central or lateral neck defines a patient as stage group II (in the absence of gross extrathyroidal extension or distant metastases) in patients aged 55 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…Following the publishing of the 8th AJCC staging system, it also caused widespread controversy. Many researchers have presented different views against the new staging system, as they consider that mETE can increase the risk of thyroid carcinoma recurrence (45). In the 8th AJCC staging system, any lymph node involvement in either the central or lateral neck defines a patient as stage group II (in the absence of gross extrathyroidal extension or distant metastases) in patients aged 55 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that mETE was strongly associated with adverse prognostic factors and reduced disease‐free survival (hazard ratio 2.8) after controlling for tumor size. mETE was found to confer a 2.24‐fold increase in risk of recurrence in all ages . Amit et al also suggested that mETE acts as a predictor of locoregional recurrence and that the distinction between gross versus microscopic ETE may not be enough to impact postoperative risk stratification .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have incorporated age into binary variables with a distinct cutoff point for DTC patients (18). In 2018, the 8th edition of the Staging System for Primary Tumors set by the American Joint Committee on Cancer adjusted the age cutoff point from 45 to 55 years, raising concerns among pathologists and clinicians (1921). Recent studies using age as a continuous variable rather than a dichotomic factor found better concordance with survival and death from TC (22, 23).…”
Section: Introductionmentioning
confidence: 99%